Pengembangan Media Pembelajaran Flipbook Digital Panduan Praktikum Sequence Of Service Pada Mata Kuliah Tata Hidang - Eliana Prisila; Nur Riska; Annis Kandriasari (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
The aim of this study is to develop a digital flipbook practikum guide of the sequence of service on course food and beverage service. Digital flipbook practical guide is much needed in practical learning because it contains multimedia elements which can be used personally by college students. This media is developed by research and development (RnD) method, employing 4D Thiagarajan, Semmel and Semmel 1974 model. The stages of this RnD study are define, design, develop, and desseminate. The result of this learning media consist 3 part is preliminary, core, and closing. this media has been validated by material expert and media expert, they value 82% for material which mean that it is very feasible and 88% for media which mean that it is very feasible. the average score of both this validation is 85% which is fall category very feasible. So it can be concluded that the digital flipbook practikum guide of the sequence of service is very feasible on course food and beverage service